Tradisi Selapanan Pada Perempuan Etnis Jawa Pasca Melahirkan di Desa Limau Manis Kecamatan Tanjung Morawa - Nizwa Putri Salsabila Gulo; Rosramadhana Rosramadhana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to examine the implementation of the selapanan tradition among Javanese postpartum women in Limau Manis Village, and to understand the meaning and community perceptions of this practice in the context of modern life. The selapanan tradition is part of local wisdom that has been passed down from generation to generation and has important value in postpartum maternal care. This study uses a qualitative method with an ethnographic approach, which allows researchers to understand cultural practices in depth through direct interaction with the community. Data collection techniques include participant observation, in-depth interviews with mothers who practice the tradition, community leaders, and traditional birth attendants, as well as documentation and field notes. The results show that selapanan is still preserved and practiced by the people of Limau Manis Village, although it has undergone several forms of adaptation to modern developments and modern medical guidelines. In its implementation, this tradition uses various natural ingredients such as parem (traditional body scrub), pilis (forehead concoction to refresh the eyes and mind), bengkungan (cloth to wrap the stomach), gerita (a kind of stagen or body binder), and the consumption of herbal medicine as part of physical care and body recovery. In addition to its physical aspects, selapanan also has a psychological dimension, providing emotional comfort and social support to postpartum mothers, thereby helping to prevent psychological disorders such as baby blues syndrome. This tradition serves not only as a form of traditional healthcare but also as a symbol of social solidarity and respect for local cultural values. Amidst the tide of modernization, preserving selapanan is crucial as a cultural identity that remains relevant. This study concludes that despite adjustments to medical developments, the selapanan tradition continues to play a significant role in maintaining maternal well-being and strengthening Javanese cultural values in the modern era.